Comparative Experimental Study of Tribo-Mechanical Performance of Low-Temperature PVD Based TiN Coated PRCL Systems for Diesel Engine. (12th December 2018) - Uddin, Ghulam Moeen; Sajid Kamran, Muhammad; Ahmad, Jawad; Ghufran, Muhammad; Asim, Muhammad; Qasim Zafar, Muhammad; Irfan, Muhammad; Waseem, Bilal; Khan, Awais Ahmad; Jawad, Muhammad; Zeid, Ibrahim; Kamarthi, Sagar
Abstract : Piston ring and cylinder liner (PRCL) interface is a major contributor to the overall frictional and wear losses in an IC engine. Physical vapor deposition (PVD) based ceramic coatings on liners and rings are being investigated to address these issues. High temperature requirements for applications of conventional coating systems compromise the mechanical properties of the substrate materials. In the current study, experimental investigation of tribo-mechanical properties is conducted for various titanium nitride (TiN) coated PRCL interfaces in comparison with a commercial PRCL system. Low-temperature PVD based TiN coating is successfully achieved on the grey cast iron cylinder liner samples. Surface roughness of the grey cast iron cylinder liner substrates and the thickness of TiN coating are varied. A comprehensive comparative analysis of various PRCL interfaces is presented and all the trade-offs between various mechanical and tribological performance parameters are summarized. Coating thickness between 5 and 6 micrometres reports best tribo-mechanical behaviour. Adhesion and hardness are found to be superior for the TiN coatings deposited on cylinder liner samples with higher roughness, i.e., 5-micron Ra. Maximum 62 % savings on the COF is reported for a particular PRCL system. Maximum 97% saving in cylinder liner wear rate is reported for another PRCL system.